INFLUENCE OF HORMONAL AND NON - HORMONAL THERAPIES ON FERTILITY AND SERUM MINERALS PROFILE OF CONCEIVING AND NON-CONCEIVING ANOESTRUS BUFFALOES - Butani, M G; Dhami, A J; Ramani, V P; Savalia , F P; Patel , M D (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A Study was carried out during breeding season on 47 anoestrus / suboestrus buffaloes to evaluate the therapeutic efficacy of hormonal and non-hormonal drugs in inducing fertile oestrus and its influence on serum macro-micro minerals profile. Fifteen true anoestrus buffaloes each were treated either with GnRH (Receptal 5.0 ml) i/m once (Gr-I) or Tono-Prepaline-Cyclomin-Lugols (TPCL) 4 times 4-5 days apart (Gr-II), while 10 suboestrus buffaloes were treated with PGF2α (Juramate 2.0 ml) i/m once (Gr-III), keeping 7 animals as untreated control (Gr-IV). The oestrus induction response and conception rate at induced oestrus in 4 groups were 86.66 & 38.46, 80.00 & 50.00, 100.00 & 40.00, and 42.85 and 66.66 %, respectively, with the oestrus induction interval of 21.50±4.59, 27.73±4.62, 3.62±0.46 and 67.50±14.49 days. The overall serum mineral profile for hormonal and non-hormonal treated anoestrus buffaloes averaged: calcium 9.47±0.15 mg/dl, phosphorus 9.66±0.14 mg/dl and magnesium 3.48±0.09 mEq/L, respectively. The values of zinc, iron, copper, cobalt and manganese were 1.85±0.09, 3.54±0.09, 0.90±0.02, 0.16±0.01 and 0.13±0.01 ppm, respectively. The serum calcium level was significantly higher in all treatment groups as compared to control group. Inorganic phosphorus was significantly higher (P
Keywords: Anoestrus buffaloes; Hormonal/Non-hormonal therapy; Fertile oestrus interval; Conception rate; Mineral profile